The Patient and the Analyst: The Basis of the Psychoanalytic Process - Sandler, Joseph; Dare, Christopher; Holder, Alex; Dreher, Anna Ursula (Karnac classics, 1992)
This is a completely revised and enlarged edition of the well-known classic by Sandler, Dare and Holder. In the twenty years since the previous edition was published much progress has been made in regard to the clinical concepts of psychoanalysis, and this new edition brings the subject completely up to date. New knowledge of the psychoanalytic process has been added, together with advances in understanding the clinical situation, the treatment alliance, transference, countertransference, resistance, the negative therapeutic reaction, acting out, interpretations and other interventions, insight, and working through. The book is both a readable introduction to the subject and an authoritative work of reference. This updated edition has been prepared by Joseph Sandler and Anna Ursula Dreher.